The Relationship Between Marital Fatigue and Attitudes Toward Infidelity: The Mediating Role of Spiritual Intelligence - Mirmohammadali, Zahra Sadat; Rajabi, Majidreza (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The aim of this study was to investigate the relationship between marital fatigue and attitudes toward infidelity, with a specific focus on the mediating role of spiritual intelligence among married university students.Methods and Materials: This descriptive-correlational study was conducted on a sample of 322 married students from Islamic Azad University, South Tehran Branch, selected using convenience sampling. Data were collected through standardized questionnaires: the 20-item Marital Fatigue Scale (Pines, 2002), the 12-item Attitudes Toward Infidelity Scale (Whatley, 2006), and the 97-item Spiritual Intelligence Scale (Motahhari, 2009). Data analysis was performed using SPSS-23 for descriptive statistics and Pearson correlation, and AMOS-21 was used for structural equation modeling (SEM) to test the mediating model.Findings: The results showed that marital fatigue was positively correlated with attitudes toward infidelity (r = .56, p < .01) and negatively correlated with spiritual intelligence (r = −.49, p < .01). Spiritual intelligence also showed a negative correlation with attitudes toward infidelity (r = −.44, p < .01). Structural model fit indices indicated a good model fit (χ²/df = 1.99, RMSEA = 0.055, CFI = 0.96, GFI = 0.94). SEM results confirmed that spiritual intelligence partially mediated the relationship between marital fatigue and attitudes toward infidelity. The direct effect of marital fatigue on attitudes toward infidelity was significant (β = 0.38, p < .001), as was the indirect effect via spiritual intelligence (β = 0.16, p < .001).Conclusion: These findings suggest that spiritual intelligence serves as a protective factor, mitigating the negative impact of marital fatigue on permissive attitudes toward infidelity. Enhancing spiritual intelligence may be an effective strategy in marital counseling and prevention of relational betrayal.